Pengaruh Kompetensi dan Independensi Terhadap Kualitas Audit Pada Jasa Audit Profesional Dalam Praktik Akuntan Publik - Valencia Baltihan Sompie; Fam Si Si; Florencia Irena Lawita (ARBITRASE: Journal of Economics and Accounting, 2026)
Audit quality is a critical factor determining the level of public trust in financial statements audited by Public Accounting Firms (KAP). This study aims to analyze the effect of auditor competence and independence on audit quality in professional audit services at KAPs. This research employs a quantitative approach with a causal-associative design. The population comprises auditors working at KAPs registered with the Financial Services Authority, with a sample of 65 respondents selected using purposive sampling from 12 KAPs located in the DKI Jakarta area. Data were collected through a five-point Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 26. The results show that competence has a positive and significant effect on audit quality, and independence likewise has a positive and significant effect on audit quality. Simultaneously, competence and independence explain 61.4% of the variance in audit quality, while the remainder is explained by variables outside the model. These findings confirm that auditors with strong knowledge, experience, and an independent mental attitude produce higher-quality audits. The results have practical implications for KAPs in designing continuous competence development programs and strengthening independence mechanisms to maintain the credibility of audit opinions.